Rethinking (Eco)Feminist Constitutionalism - Silvina Alvarez Medina (Athena)
This article focuses on the developments of liberal constitutionalism vis a vis the challenges posed by feminist and ecofeminist constitutionalism. First, it explores the insufficiencies of contemporary constitutionalism for fully incorporating the gender perspective. Second, it proposes two key notions for capturing the feminist proposal towards a new reading of the constitution: the relational perspective and the vulnerable self. Along with the relational approach and the review of autonomy in the light of vulnerability, the article proposes a constitutional reflection on the axiological basis of the constitution.